2002
DOI: 10.1659/0276-4741(2002)022[0032:fetsdo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Explaining the Spatial Distribution of Hillslope Debris Flows

Abstract: This article was prepared with the support of the following research projects: "Debris fall assessment in mountain catchments for local end-users-DAMO-CLES" (EVG1-1999-00027P), financed by the European Commission, and "Assessment of sediment sources and runoff generation areas in relation to land-use changes-HIDROESCALA" (REN2000-1709-C04-01/GLO), financed by CICYT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 19 publications
1
24
0
4
Order By: Relevance
“…The other soil parameters were evaluated as, for soils 1 and 2: soil cohesion 4.42 and 4.13 kPa; angle of friction 29.8° and 29.7°. Depth to the shear surface was set at 0.85 m. Landslides were precluded from occurring at slopes less than 25° and more than 50°, in good general agreement with the survey of Lorente et al (2002) which showed most debris flows to be on 2035° gradients. Landslides which occurred in the first 24 hours of the simulation were eliminated as indicating squares defined as unconditionally unsafe.…”
Section: Landslide Calibrationsupporting
confidence: 60%
See 2 more Smart Citations
“…The other soil parameters were evaluated as, for soils 1 and 2: soil cohesion 4.42 and 4.13 kPa; angle of friction 29.8° and 29.7°. Depth to the shear surface was set at 0.85 m. Landslides were precluded from occurring at slopes less than 25° and more than 50°, in good general agreement with the survey of Lorente et al (2002) which showed most debris flows to be on 2035° gradients. Landslides which occurred in the first 24 hours of the simulation were eliminated as indicating squares defined as unconditionally unsafe.…”
Section: Landslide Calibrationsupporting
confidence: 60%
“…The scenario results can all be explained by physical reasoning. In addition they match the analysis by Lorente et al (2002) of debris flow occurrence in the flysch sector containing the Ijuez catchment. This analysis found the distribution of debris flows to be higher in reforested areas (31%), shrublands (24%) and areas with natural pine forest (20%) compared with meadow lands (7%).…”
Section: Scenario Simulationsmentioning
confidence: 65%
See 1 more Smart Citation
“…Glade 2003). Forest clearing, for example, may dramatically accelerate shallow landsliding in steep terrain (e. g. Montgomery et al 2000;Lorente et al 2002;Barthurst et al 2007). In general, however, susceptibility to mass movements is mainly controlled by the local lithology and (especially) topography (e.g.…”
Section: Mass Movementsmentioning
confidence: 99%
“…La pendiente media se aproxima al 20% y las mayores pendientes (43%) se localizan en laderas con exposición norte. El sustrato geológico sobre el que se asienta está formado por dos grandes unidades: (i) en la parte superior predomina el flysch eoceno surpirenaico, constituido por una alternancia de areniscas carbonatadas y margas, afectado por pequeños deslizamientos que en algunas ocasiones pueden dar lugar a grandes movimientos en masa (Lorente et al, 2002); (ii) en la parte baja y media predomina la marga de Larrés, compuesta principalmente por minerales arcillosos (44% de illita y clorita), carbonatos, con un elevado contenido de calcita y dolomita (41%) y cuarzo (15%). Además, se pueden observar pequeñas capas de areniscas y núcleos de concreciones carbonatadas.…”
Section: áRea De Estudiounclassified